Comparison of coinciding anticipation timing and reaction time performances of adolescent female volleyball players in different playing positions - Günay, A. R.; Ceylan, H. I.; Çolakogolu, F. F.; Saygin, Ö. (The Sport Journal, 2019)
The purpose of this study was to compare coinciding anticipation timing (CAT) and reaction time performance of adolescent female volleyball players in different playing positions. Twenty-eight adolescent volleyball players (14 Outside players and 14 Middle players), who played volleyball in licensed infrastructure leagues and trained 5 days a week regularly, with an average age of 15.0 ± 0.94 years, participated voluntarily. A Bassin Anticipation Timer was used to measure the CAT performance of the volleyball players at different stimulation speeds: Slow- 3 mph (1.34 m/s) and Fast- 8 mph (3.58 m/s). Visual, auditory, and mixed reaction times were measured with the Newtest 1000 Instrument. When the absolute error scores of volleyball players were compared according to playing positions, a statistically significant difference was found in the fast speed condition (t = -2.090, p = .047). A statistically significant difference was also observed in the mixed reaction time scores (t = -2.163, p = .040). Middle players had better CAT scores in the Fast condition and mixed reaction time performances than outside players. This is thought to be due to the different responsibilities of middle players in the game as compared with outside players. Because both offensive combinations and block responsibilities are more diversified for Middle players, CAT and reaction time performance of middle players are of greater importance. In order to reach top level performance, it is thought that a number of special exercises, in addition to volleyball training, should be done to improve the CAT performance. It is recommended to repeat the research in different age groups, different categories and different positions.